ENKRIPSI CITRA DIGITAL MENGGUNAKAN KOMBINASI ALGORITME HILL CIPHER DAN CHAOS MAP DENGAN PENERAPAN TEKNIK SELEKTIF PADA BIT MSB - Devi Ratnasari; Hajar Puji Sejati (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2017)
This paper represents a digital image encryption algorithm using a combination of hill cipher and chaos map algorithms. The hill cipher algorithm is one of the coding techniques by applying a square matrix as an encryption key. In this paper, the key matrix used is a 3x3 invertible matrix. While chaos map technique chosen is Logistic Map technique as a random number generator that will be used as keystream. Application of selective encryption techniques to MSB bits (Most Significant Bit) is also used to reduce computing by only performing operations on four major bits of each RGB pixel (Red, Green and Blue). To encrypt, an image is first mapped based on RGB color components (Red, Green and Blue) and then encrypted using a hill cipher key matrix. The encryption result on each RGB channel is then selected four bits MSB from each pixel and then XOR with keystream as a result from Logistic Map. Experimental results performed on multiple color images show that the image can be succesfully encrypted. It can be seen from the resulting histogram is flat on each RGB channel of the encrypted image, the average value of entropy is 7.99 and the correlation value is close to 0.